THU0589 Collaborative Development of Paediatric Musculoskeletal Matters (PMM) – An Online Evidence Based Information Resource for Paediatric Musculoskeletal Medicine. (9th June 2015) - Smith, N.; Jandial, S.; Rapley, T.; Foster, H.
Abstract : Background: Our unit has developed a range of educational resources focused on supporting healthcare professionals in their assessment of children and young people (CYP) presenting with musculoskeletal problems. Whilst these resources (including pGALS [1] and pREMS [2]) are increasingly taught at UK medical schools, we identified need to support dissemination and impact of these resources to healthcare professionals and especially to those who are not "specialists" in paediatric musculoskeletal medicine. Objectives: The aim of this research was to develop an electronic resource to host educational materials in a format appropriate to the needs of end-users. Methods: Engagement with stakeholder groups in primary care, paediatrics, musculoskeletal specialties and medical students informed essential "core" learning outcomes [3, 4] to derive content. Representatives from the same stakeholder groups, social science and web development experts transformed the learning outcomes into a suitable framework for an electronic resource, entitled paediatric musculoskeletal matters – pmm. Target audience representatives reviewed the framework and user opinion was gathered using an online survey (n=74) and two focus groups (n=15). Experts in paediatric musculoskeletal medicine working in other institutions further peer reviewed the finalised content and design. Results: User preferences (e.g. site access, function, content, format) informed design with mobile, tablet and web compatible versions to facilitate access, various media and formats (e.g. videos, interactive cases, signposting, summaries) to engage users and the content presented in modules (i.e. Clinical assessment, Investigations and management, Limping child, Joint pain by site, Swollen joint(s) and Resources). Video demonstrations of pGALS and pREMS with many "top tips" and links to recommended resources and websites are provided. Conclusions: Our collaborative and evidence based approach to develop pmm (pmmonline.org) with engagement of end users and stakeholders aims to ensure that the final resource will address their needs. Work to evaluate pmm (dissemination, user experience, clinical impact) is in progress. Pmm is targeted at medical students and primary care although messages are transferable to all health care professionals involved in the care of CYP; further versions of pmm (e.g. pmm for nurses and pmm for other health care environments) are to be launched later in 2015. References: Foster H, Jandial S. pGALS-paediatric Gait Arms Legs and Spine: a simple examination of the musculoskeletal system. Pediatric Rheumatology 2013;11:44. Foster H, Kay L, May C, Rapley T. Pediatric regional examination of the musculoskeletal system: a practice and consensus based approach. Arthritis Care & Research 2011;63(11):1503-1510. Goff I, Boyd D, Wise E, Jandial S, Foster H. Paediatric musculoskeletal learning needs for general practice trainees: achieving an expert consensus. Education for Primary Care 2014, 25, 249-256. Jandial S, Stewert J, Kay L, Foster H. Paediatric musculoskeletal learning outcomes for medical students (paper in review). Disclosure of Interest: None declared